Effect of Temperature on Buckling of Composite Materials Column: Effect of Temperature on Buckling of Composite Materials Column - Resan, Kadhim K.; Ali, Mohammed H.; Faheed, Noor K. (Al-Nahrain Journal for Engineering Sciences, 2017)
A theoretical and experimental investigation pertaining to the buckling behavior of slender fiber reinforced polymer columns subjected to axial loading under varying temperatures (from room temperature to 50?). Two groups of composite materials were used for manufacturing of test specimens, the first consist of perlon fiber as a reinforcement and acrylic resin as a bonding matrix, while the second consists of a combination of perlon and carbon fibers as reinforcement. The composite specimens were fabricated by vacuum molding technique and cut according to ASTM D-638 for conducting tensile test. The data from tensile test were used to calculate the effective slenderness ratio and defining the column as Euler buckling column. An experimental rig was designed, manufactured and calibrated to study the effect of thermal and buckling load subjected to columns.Numerical analyses pertaining the buckling behavior for both groups were conducted. The results show that the temperature has a considerable effect on properties of fiberreinforced polymer composites where the value ofcritical load and Young’s Modules decrease withthe increase of temperature for both groups.Perlon & Carbon reinforcement composites gavebest mechanical properties, which make them thebest candidate to improve the buckling resistancecharacteristics of composite materials.